2007
DOI: 10.1111/j.1572-0241.2007.01341.x
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Colitis Has a Worse Prognosis When Isolated to the Right Side of the Colon

Abstract: A total of 273 cases of biopsy-proven ischemic colitis were identified of which 71 (26.0%) involved only the right side. Patients with IRCI had a worse outcome than those with colon ischemia involving other colon regions, including a fivefold need for surgery and a twofold mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 11 publications
(11 reference statements)
7
106
0
2
Order By: Relevance
“…Low-flow states may be induced by arrhythmias or cardiac dysfunction, drugs, dehydration or (aortic) surgery. Isolated right-sided ischemic colitis usually presents with abdominal pain, but rarely with bloody diarrhea [50] . Right-sided ischemic colitis is usually associated with SMA stenosis or occlusion.…”
Section: Ischemic Colitismentioning
confidence: 99%
“…Low-flow states may be induced by arrhythmias or cardiac dysfunction, drugs, dehydration or (aortic) surgery. Isolated right-sided ischemic colitis usually presents with abdominal pain, but rarely with bloody diarrhea [50] . Right-sided ischemic colitis is usually associated with SMA stenosis or occlusion.…”
Section: Ischemic Colitismentioning
confidence: 99%
“…Segmental colon ischemia was initially recognized over 50 years ago, 16 and it results from numerous heterogeneous factors. 1,17 More recent studies revealed important distinguishing features of RSCI compared with colon ischemia involving other sites, including the predominance of pain over bleeding, 1 and higher rates of comorbidities, including coronary artery disease, 4,5 atrial fibrillation, 6 and dialysis dependency. [3][4][5][6] Patients with extension …”
Section: Discussionmentioning
confidence: 99%
“…In the past, authorities ascribed little role to angiography in colon ischemia, 2 and use of angiography was not reported in more recent descriptions of RSCI. [3][4][5][6][7] Chronic mesenteric ischemia preceding RSCI could have been overlooked because patients with RSCI typically present to Emergency Departments where physicians may focus on their acute symptoms and not recognize previous abdominal angina. A case report describes a 64-year-old American woman who had initial colon ischemia of unstated distribution, subsequent left-side colon ischemia, and previous chronic abdominal pain who underwent stenting of celiac artery and IMA stenoses.She was pain-free 12 weeks later.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This classification system was chosen because of the prognostic importance of non-ILIC. 7,8 Resoution day was defined the point when patients did not feel pain and started general diet.…”
Section: Definition Of Non-ilic and Ilicmentioning
confidence: 99%